Meta Analysis of the Relationship of Obesity with Type 2 Diabetes Mellitus in Indonesia - Akhmadi Abbas (Universitas STRADA Indonesia, 2021)
Diabetes mellitus is a world public health problem. This study aims to determine the relationship between obesity and the incidence of type 2 diabetes mellitus in Indonesia. A systematic review and meta-analysis were carried out on case control studies published in the google scholar database. Data processed using RevMan 5.4. Pooled odds ratio (OR) is calculated by fixed effect models. Meta-analysis results showed that there was a significant relationship between obesity and the incidence of type 2 diabetes mellitus (p = 0.00001, OR 4.99, 95% CI 3.58-6.96)). There is a significant relationship between obesity and the incidence of type 2 diabetes mellitus. Obese people have a 4.99 times greater risk of suffering from type 2 diabetes mellitus in the case group than the control group. The public is expected to manage their obesity so that they can reduce the risk of suffering from diabetes mellitus